Metacognitive reading strategies: gender, locality, and age differences among secondary school students - Odofin, Toyin; Urien, James; Obro, Sunday (Intelektual Pustaka Media Utama, 2024)
This study ascertained the influence of gender, locality and age on metacognitive reading strategies of secondary school students. The sample size consists of 440 students randomly selected from 23 secondary schools. An adopted questionnaire tagged “metacognitive reading strategies questionnaire,” was used as the data gathering instrument, with a logical validity of 0.88 and Cronbach alpha of 0.73 as internal consistency. The data collected were analysed statistically using descriptive statistics and t-tests. Data analysis revealed that females' reading strategies outnumber males'; females' global strategies ranked highest, while females' problem-solving strategies ranked lowest; and students in urban secondary schools tended to utilise metacognitive reading strategies more frequently than their rural counterparts. This study also shows that students with higher age brackets make more use of metacognitive reading strategies than lower-age students. Therefore, it is recommended that educators should be prepared to educate students how to effectively utilise various components of metacognitive reading strategies.